Plan Stratégique 2007-2010 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Ce plan stratégique 2007-2010 du CTA met l'accent sur l'efficacité et la durabilité..